2019
DOI: 10.1186/s12944-019-1103-7
|View full text |Cite
|
Sign up to set email alerts
|

4-cholesten-3-one decreases breast cancer cell viability and alters membrane raft-localized EGFR expression by reducing lipogenesis and enhancing LXR-dependent cholesterol transporters

Abstract: Background The alteration of lipid metabolism in cancer cells is recognized as one of the most important metabolic hallmarks of cancer. Membrane rafts defined as plasma membrane microdomains enriched in cholesterol and sphingolipids serve as platforms for signaling regulation in cancer. The main purpose of this study was to evaluate the effect of the cholesterol metabolite, 4-cholesten-3-one, on lipid metabolism and membrane raft integrity in two breast cancer cell lines, MCF-7 and MDA-MB-231. Its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…The activation of LXR seems to decrease the CSCs invasion and migration. These results could be related to the role of CHOL is an important component of membrane lipid rafts containing the signaling molecules precipitating in cell migration [ 16 , 32 , 33 ]. Moreover, ABCA1 modulates CHOL distribution in the membrane which affected the pathways promoting cell migration [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The activation of LXR seems to decrease the CSCs invasion and migration. These results could be related to the role of CHOL is an important component of membrane lipid rafts containing the signaling molecules precipitating in cell migration [ 16 , 32 , 33 ]. Moreover, ABCA1 modulates CHOL distribution in the membrane which affected the pathways promoting cell migration [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…To confirm this effect, LXRs inverse agonist and LXRβ knockdown were employed, which resulted in the neutralization. Further study showed that 78 decreased the viability of two breast cancer cell lines, namely MCF-7 and MDA-MB-231, exerting promising antibreast cancer activity by altering LXRs-dependent lipid metabolism in breast cancer cells without increasing lipogenesis ( Elia et al, 2019 ). Gorgostane-3β,9α,5α,6β,11α-tetrol (79) and gorgost-5-ene-3β,9α,11α-triol (80) isolated from the Plexaura species possessed a better affinity with LXRα than LXRβ with EC 50 values of 0.45 and 0.05 μM ( Jayasuriya et al, 2005 ).…”
Section: Natural Products Targeting Liver X Receptorsmentioning
confidence: 99%
“…Cholesterol oxidase is a FAD-dependent (flavin adenine dinucleotide) enzyme that catalyzes the oxidation and isomerization of sterols to sterones, typically cholesterol (5-cholesten-3- β -ol) to 4-cholesten-3-one (cholestenone) ( Lashgarian et al, 2016 ; Pan et al, 2011 ; Sakodinskaya and Ryabov, 2000 ). Studies have shown that cholestenone, which is produced as a metabolite, is safe and can be used to control obesity, treat liver disease, and prevent keratinization of the skin ( Elia et al, 2019 ). Wali et al (2019) isolated Bacillus pumilus W1 and Serratia marcescens W8 from soil contaminated with oil and reported that these strains degrade cholesterol and produce red colonies in M9 medium containing 0.1% cholesterol as the only carbon source.…”
Section: Resultsmentioning
confidence: 99%